2008
DOI: 10.1590/s1415-98482008000100002
|View full text |Cite
|
Sign up to set email alerts
|

"Aposentadorias e Pensões" e desigualdade da renda: uma análise para o Brasil no período 1998-2003

Abstract: Este trabalho tem como objetivo avaliar a contribuição do componente do rendimento domiciliar "aposentadorias e pensões" para a desigualdade da distribuição do rendimento domiciliar per capita no Brasil, nos meios rural e urbano, em 1998, 1999, 2001, 2002 e 2003. Para isso, utilizaram-se estratos de rendimento domiciliar per capita e a metodologia de decomposição do índice de Gini dos seguintes componentes: rendimento do trabalho principal, rendimento de outros trabalhos, aposentadorias e pensões, doações, ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
(2 reference statements)
0
5
0
2
Order By: Relevance
“…30 It was found that elderly individuals with dementia contributed to 28.2% of the family income, in accordance with studies which have shown that the share of pensions and benefits in total household income is increasing progressively in Brazil. 31 In the assessment of the sociodemographic data of the primary caregivers of elderly people with advanced dementia, it was found that they are mostly female aged 53.2 years on average. They are mostly the children of patients, married, have 7.8 years of formal education, and 32 Figueiredo and Souza (2008) evaluated 52 patients with dementia in Portugal, 61.5% of whom were completely dependent, and noted that 67.7% of the caregivers were aged between 41 and 60 years, 88.5% were female, 51.9% were the patients' children, 75% were married, 53.8% had up to 4 years of education, and only 25% were employed.…”
Section: Discussionmentioning
confidence: 99%
“…30 It was found that elderly individuals with dementia contributed to 28.2% of the family income, in accordance with studies which have shown that the share of pensions and benefits in total household income is increasing progressively in Brazil. 31 In the assessment of the sociodemographic data of the primary caregivers of elderly people with advanced dementia, it was found that they are mostly female aged 53.2 years on average. They are mostly the children of patients, married, have 7.8 years of formal education, and 32 Figueiredo and Souza (2008) evaluated 52 patients with dementia in Portugal, 61.5% of whom were completely dependent, and noted that 67.7% of the caregivers were aged between 41 and 60 years, 88.5% were female, 51.9% were the patients' children, 75% were married, 53.8% had up to 4 years of education, and only 25% were employed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the survey results, income derived from social security accounted for the second largest share of income in the Gini coefficient calculation, behind only primary job income. Following the same line of reasoning, Ferreira and Souza (2008) analyzed PNAD data for the years 1998 to 2003 and demonstrated the substantial contribution of social security benefits to income distribution inequality in Brazil. Similarly, Hoffmann (2009) evaluated data from the 2007 PNAD and found that official retirement and pensions are slightly regressive.…”
Section: Empirical Evidence Of the Socioeconomic Impact Of Retirementmentioning
confidence: 97%
“…Important studies on the impact of retirement and pensions on income distribution inequality have been conducted by Hoffmann (2003Hoffmann ( , 2009), Ueda (2005), Afonso and Fernandes (2005), Cavalieri and Pazello (2005), Ferreira (2006), Ferreira and Souza (2008), Silveira (2008) and Rangel (2011). Each of these studies adopted the Gini coefficient decomposition method, either by analyzing the various components of household income or by calculating the internal rates of return (IRRs) provided by social security contributions and benefits.…”
Section: Empirical Evidence Of the Socioeconomic Impact Of Retirementmentioning
confidence: 99%
See 2 more Smart Citations